Proppant immobilization facilitated by carbon nanotube mediated microwave treatment of polymer-proppant structures - Gomez, Virginia; Alexander, Shirin; Barron, Andrew R. (Colloids and surfaces. A, Physicochemical and engineering aspects, 2017)
[Display omitted] •MWCNTs facilitate the aggregation of coated proppants through localized microwave heating.•Covalently functionalized proppants are used as linkage points for polymer coatings.•MWCNTs result in melting of the coating under microwave irradiation joining the particles. The application of multi-walled carbon nanotubes (MWCNTs) to facilitate the aggregation of ceramic particles (proppants) by embedding in the coating through localized microwave heating is reported. Thermogravimetric analysis (TGA), scanning electron microscopy (SEM) along with energy dispersive X-ray analysis (EDX) and atomic force microscopy (AFM) were used to characterize a series of covalently functionalized proppants with carboxylic acids (lysine and fumaric acid). The bi-functional acids allow for a controlled reaction with a coating (resin and polymer). The addition of carbon nanotubes results in the melting of the coating under exposure to microwave irradiation (20s @ 100W) joining the particles. The significant reduction in reaction time (compared to the thermal treatments of 2–24h) is due to the presence of the MWCNTs. The microwave heating of the MWCNTs can thus be used to create interaction and adhesion between functionalized particles subject to a specific stimulus.